Robusta Coffee Decreased Malondialdehyde Levels in Wistar Mice Experiencing Oxidative Stress - Abidah, Rahmi Syarifatun; Wirjatmadi, Bambang; Purwanto, Bambang; Adriani, Merryana (Health Notions, 2017)
Coffee drinking is a habit that still doubtful for itâs benefits. Many active ingredients in robusta coffee (Coffea canephora) are very useful for health, especially the antioxidant content that can ward off free radicals that absorbed in the body. Free radicals can be caused by psychological stress exposure. Excessive amounts of radicals in the body cause oxidative stress. This study aimed to see the robusta coffee effect on decreasing levels of Malondialdehyde (MDA) with ârandomized post test only control groupâ design with 25 samples of white male rat strain wistar (Rattus norvegicus). Samples were divided into 5 groups: control groups and randomized treatment groups. Treatment given in psychological stress and giving robusta coffee drink with single dose. This study used âone way anovaâ test and followed by âpos hoc tukey HSDâ test for statistics. Robusta coffee had an effect in MDA levels changing. There was a MDA levels decreasing in 1 hour after robusta coffee drinking in experimental rats with oxidative stress conditions that were exposed by psychological stress.